System of psycho-therapeutics influences in patients admitted to hospital with cardiovascular diseases. - Teresa Rodríguez Rodríguez; Juan José Navarro López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Fundaments: Within the restricted field of the patients' psychological environment, anxiety and depression seem ti play an important role although it is still pending how to clear it up definitely in the case of ischemic cardiopathy and coronary diseases. However, it isostensible that the patients who suffer from cardiovascular diseases frequently present psychological disorders, mainly emotional ones. Objective: To assess the effectiveness of a system of psychotherapy influences in patients with cardiovasular diseases. Method: Intervention study witha cuasi experimental design in patients with cardiovascular urgencies hospitalized at the Integral Care Unit of the Heart of the ¨Dr. Gustavo A. Lima¨ Hospital from June 1st 2002 to june 1st 2003 and who received relaxing, stimulating and sleeping treatment. Psychological and physiological modifications were assessed after having received treatment with these psychological techniques. Result: Acute Myocardial infarction and Angina pectoris were the most common causes of admission. The variation of respiratory and cardiac frequency as well as blood pressure tend tomaintain, diminish or keep normal values. The psychological state of the patient was favoured after treatment. Conclusion: The effect of the system of psychotherapy influences were beneficial both organically and psychologically.